Spatial modeling of nitrogen and phosphorus in an agricultural basin in northeastern Brazil (Research, Society and Development, 2022)
Hydrological models can help in predicting the behavior of aquatic systems in watershed, and are able to simulate both hydrological processes and nutrient dynamics. The SWAT model is used in water resource management to estimate the production of water, sediments, and nutrients, as well as to identify diffuse sources of pollution. The objective of this work was to evaluate spatial and temporal variability in the dynamics of the nutrients nitrogen and phosphorus derived from agricultural activities, at the sub-basin level, in the watershed of the Poxim-Açu River. The model was subjected to tests of sensitivity, calibration, and validation in terms of the discharge and the behavior of the nutrients. Statistical analysis showed that the performance of the model was satisfactory. It was found that more than 40% of the areas of the main subbasins that produced sediments and nutrients was occupied by pasture, and that the predominant soil types were Red-Yellow Argisols and Gleysols. These subbasins corresponded to 30% of the hydrographic basin studied and produced 65% of the sediments, 84% of the total nitrogen, 93% of the phosphate, and 86% of the total phosphorus.